Adoption of Voice User Interfaces in Controlling In-Vehicle Features, Understanding Key Influencing Factors and Creating Design Guidelines for Replacing Physical Controls - Hu, Siyuan; Tao, Jiawei (My University, 2025)
Contemporary vehicles are usually equipped with numerous interior features with complicated designs, which usually results in higher energy consumption, safety issues related to distractions, and a shorter service life due to the overreliance on screens and complicated interfaces. To address this issue, it is necessary to develop a concept to reduce the number of interior features. The purpose of this thesis is to investigate whether the VUI (voice user interface) has the ability to replace the physical controls in operating driving task during driving. Three research questions guide this investigation. The literature review employs Desmet’s Product Emotion and Experience theories as a foundation for understanding VUI, alongside an analysis of the current state of VUI research. A mixed-method approach was used to explore user perspectives, incorporating qualitative and quantitative data collected through questionnaires, interviews, and statistical analysis. The findings reveal that participants expressed a more positive attitude toward using VUI for secondary and tertiary driving tasks, while showing reluctance for primary driving tasks. Based on these insights, a User Perception Mechanism and a Decision-Making Model were developed, accompanied by design guidelines. A comparative experimental study identified specific physical controls that could be replaced by voice interaction. These findings informed the creation of use scenarios and the development of a concept —a car key fob inte grated with VUI, which was visualized with 3D design tools. The results suggest that VUI has significant potential to support controlling driving tasks features, enhance user experience, and contribute to the development of future intelligent car cockpits.
Keywords: Voice User Interface; User Experience; Industrial Design; Interaction Design; Automotive; Driving tasks